Nefunkční rodina v současné literatuře pro mládež - Láníková, Dominika (Univerzita Pardubice, 2021)
This diploma thesis focuses on the theme of dysfunctional families in contemporary young adult literature. With the aid of scholarly literature, the basic concepts of young adult literature, along with themes, presenting the portrayal of the complex subject of family in young adult literature, and features that can contribute to family being seen as dysfunctional, in conjunction with trauma studies in literature, are described in the first half of the paper. On the basis of this theoretical framework, the other half of this paper analyses two selected young adult novels; Holding Up the Universe written by Jennifer Niven, and Far from the Tree written by Robin Benway. The analysis focuses on the portrayal of the families in the selected novels, along with their presentation of characteristics, style of writing, settings, narrator, as well as depiction of the dysfunction of families and trauma portrayed in the novels.
Dysfunctional Family in Contemporary Young Adult Literature
Keywords: young adult literatura; literatura pro děti a mládež; rodina; trauma; nefunkční rodina; coming-of-age romány; literatura traumatu; Niven, Jennifer; Tíha Vesmíru (Holding Up the Universe); Benway, Robin; Far from the Tree; young adult literature; family; trauma; dysfunctional family; young adult novel; coming-of-age novel; writing trauma; Niven, Jennifer; Holding Up the Universe; Benway, Robin; Far from the Tree